Adaptation of E-learning during the Pandemic Towards Face-to-Face Classroom Learning - Widiastuti, Widiastuti; Biduri, Febi Nur; Ernawati, Eka Yuniar; Harun, Yessy (Ridwan Institute, 2024)
The COVID-19 pandemic has prompted a significant shift in the Education Dynamics landscape, necessitating a move from traditional face-to-face learning to distance learning (e-learning). In the aftermath, this research focuses on the dynamics of students readjusting to face-to-face learning. The study, employing both quantitative and qualitative analyses, includes a field study with 56 Management study program students. Objectives include exploring how students adapt to resuming face-to-face learning and emphasizing direct interactions. Preliminary findings reveal a positive inclination towards face-to-face learning, though challenges like long commutes and financial burdens persist. The research suggests addressing these concerns to enhance the overall educational experience. A notable trend is the preference for a hybrid approach, combining online and face-to-face sessions, indicating a desire for increased efficiency and an enhanced learning experience. In conclusion, the study contributes insights for educational institutions to optimize the post-pandemic learning environment, considering both positive experiences and challenges faced by students.